The Influence of Company Financial Characteristics on Banking Dividend Payments Listed on The Indonesian Stock Exchange - Keysha Alea Oktaviana; Birdgitta Jasmine Maharani Hapsan; Farah Margaretha Leon (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
This study aims to examine the impact of variables affecting dividend payouts in banking companies listed on the Indonesia Stock Exchange. The addition of financial distress as an independent variable represents a novel aspect of this research. A purposive sampling method was used to select 23 banking companies over five years (2019–2023), yielding 115 data points analyzed through panel data regression. The results show that leverage, liquidity, and firm size have no effect on dividend payout, while profitability and financial distress have a significant influence. Financial managers should evaluate the company's financial condition and con-sider factors such as leverage, liquidity, profitability, firm size, and financial distress when making dividend payout decisions. Likewise, investors should consider financial performance indicators, particularly in companies with larger, stable assets, which offer long-term returns and higher profitability. This enables investors to assess potential and make informed investment decisions.